2015
DOI: 10.1890/14-0548.1
|View full text |Cite
|
Sign up to set email alerts
|

Are large macroalgal blooms necessarily bad? nutrient impacts on seagrass in upwelling‐influenced estuaries

Abstract: Knowledge of nutrient pathways and their resulting ecological interactions can alleviate numerous environmental problems associated with nutrient increases in both natural and managed systems. Although not unique, coastal systems are particularly prone to complex ecological interactions resulting from nutrient inputs from both the land and sea. Nutrient inputs to coastal systems often spur ulvoid macroalgal blooms, with negative consequences for seagrasses, primarily through shading, as well as through changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 87 publications
(84 reference statements)
3
13
0
Order By: Relevance
“…However, the lack of a direct NO 3 toxicity effect in this experiment is consistent with previous work where plants exposed to 1000 μM NO 3 or NH 4 exhibited no detectable stress or mortality (Kaldy 2012). Likewise, Hessing-Lewis et al (2015) exposed eelgrass plants to very high nutrient loads and found little evidence for nutrient effects. Some seagrass populations may be more susceptible to thermal or other stressors than to direct nutrient stressors.…”
Section: Community Structuresupporting
confidence: 91%
“…However, the lack of a direct NO 3 toxicity effect in this experiment is consistent with previous work where plants exposed to 1000 μM NO 3 or NH 4 exhibited no detectable stress or mortality (Kaldy 2012). Likewise, Hessing-Lewis et al (2015) exposed eelgrass plants to very high nutrient loads and found little evidence for nutrient effects. Some seagrass populations may be more susceptible to thermal or other stressors than to direct nutrient stressors.…”
Section: Community Structuresupporting
confidence: 91%
“…What are some of the possible explanations for the preponderance of regional‐scale patterns in eelgrass community structure in these estuaries? Considering primary producers first, we know from previous observational and experimental work in these estuaries that eelgrass and macroalgal abundances are largely influenced by ocean upwelling rather than competition with other primary producers (Hessing‐Lewis et al , ; Hessing‐Lewis and Hacker ). We found similar patterns in this study; the two estuaries with greatest upwelling intensity (i.e., YB and CB) had much lower eelgrass shoot densities and biomass than the estuary with less upwelling exposure (NB; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These pressed subsidies affect biogeochemical processes that alter habitat suitability for benthic fauna, may change over different temporal scales (Nedergaard et al ) and thus may explain temporal variability in the effects of macroalgal subsidies on benthic communities (Raffaelli ). Pressed macroalgal subsidies may alter abiotic conditions by restricting light (Olyarnik and Stachowicz ) and oxygen availability (Hessing‐Lewis et al ). Furthermore, hypoxic and anoxic conditions caused by pressed macroalgal mats alter nutrient cycling (Havens et al ) and, coupled with the release of organic matter during macroalgal decomposition, result in elevated concentrations of hydrogen sulfide (Hargrave et al ).…”
mentioning
confidence: 99%